Environmental politics and policy in the West - Smith, Zachary A., editor; Freemuth, John, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
This new edition offers a comprehensive and current survey of major western policy and environmental issues. Contributors address the policy process as it affects the states in the region, and how bureaucracy and politics shape environmental dialogues in the West.
Preface / Zachary A. Smith and John Freemuth -- Energy, the environment, and the American West: a policymaking perspective / Leslie R. Alm -- Bureaucracy and politics of energy and environmental policy in the western states / Matthew A. Cahn, Sheldon Kamieniecki, Denise McCain-Tharnstrom and Duran Fiack -- Governance, science, and the federal lands / John Freemuth and Esther Babcock -- Urban planning and environmental policy in the West / Hugh Bartling, Matt Lindstrom and Ashleigh Walter -- Renewable energy policymaking in the American West / Charles Davis, Sandra Davis and Cassandra Koerner -- Water in the western United States: storied past and troubled future / Zachary A. Smith -- The politics of river restoration / Daniel McCool -- Wildlife conservation policy and energy development in western States / William R. Mangun and Jean C. Mangun -- Tribal sovereignty: the struggle to balance traditions of environmental stewardship with modern-era energy resource development / Robert E. Forbis Jr. and Megan M. DeMasters.
Third edition.
Keywords: Environmental policy -- West (U.S.)